Transpalatal bone distractor as an option for maxillary expansion: Case report (Research, Society and Development, 2021)
Transverse maxillary discrepancy is commonly observed in patients seeking orthodontic treatment for adequate occlusion. Is defined with a posterior crossbite and anterior crowding. Several devices are available to address this discrepancy and achieve maxillary expansion, that can be achieved through surgical and non-surgical techniques. Surgical procedure is indicated when the patient has reached skeletal maturity, in this way it is possible to reach the correct size of the maxilla using dento-mucus-supported, dento-supported and bone-supported devices. In the present case, the use of a bone-supported device shows the advantages over the other techniques since there is no damage to tissues or dental elements showing only effects to bone tissues resulting in a significant increase in the maxillary arch and a better occlusion in addition to respiratory improvement.